Sequential estimation / Malay Ghosh, Nitis Mukhopadhyay, Pranab K. Sen - Ghosh, Malay (Wiley series in probability and statistics. Probability and statistics, 1996)
This book devoted to sequential estimation presents the advances of the past fifteen years including those in the areas of three--stage accelerated sequential sampling procedures. It integrates the diversities in sequential estimation in a logical, treating both classical and modern techniques and including parametric and nonparametric methods.